The Case of the Sidekick: The Roles of Dr. John Watson in Sherlock Holmes Canon by Sir Arthur Conan Doyle - Adiba Qonita Zahroh (Universitas Gadjah Mada, 2015)
sidekick in literature is perceived as a supporter of a hero or a man-behind a hero. However, it does not always work that way. In Sherlock Holmes canon, there can be found a well-known dr. John Watson who acts differently as a sidekick for Sherlock Holmes as a protagonist of the stories. Throughout the canon, Watson does not merely act as a supporter or a man-behind who just follows Holmes’s moves. In many occasions, Watson contributes varied significant things in supporting Holmes through some roles he possesses. Moreover, what Watson contributes is found out to be influential to Holmes. Therefore, it can be seen that being a sidekick can do other things apart from following the hero all the time.Based on the facts about Watson’s contributions, this paper is conducted to examine the roles dr. John Watson as a sidekick. The data used in the research are 56 short stories and four novels of Sherlock Holmes bundled together in Sherlock Holmes canon. The method of collecting the data is executed through intensive reading, mapping out the roles of dr. John Watson found during the reading process, and analysing the collected data.Since the focus of this paper is about dr. John Watson’s roles and their influences towards Sherlock Holmes, objective theory is chosen to be employed. Related to the theory, this paper offers the explanation of intrinsic elements with focus on character element and sidekick character.